Pengaruh Pemberian Fungi Mikoriza Arbuskula (FMA) Terhadap Kandungan Logam Timbal (Pb) pada Tanaman Sengon (Paraserianthes falcataria) - Juneith O S Nadeak; Delvian Delvian; Deni Elfiati (Program studi Kehutanan USU, 2015)
Plumbum (Pb) is an environmental contaminant that risk for human’s health, reducing soil fungtion and productivity and damage for plants. Therefore, remediation is need to do such as bioremediation using AMF and sengon as a host. A research was conducted to knowing the effect of the addition of AMF for Pb content on Sengon in green house of Agriculture USU. Analyze of Pb metal was done at Research Laboratory of Pharmacy USU on October 2014- February 2015 using faktorial completely randomize design with two faktors, i.e Pb addition (0 and 400 ppm) and doses of mycorrhiza inoculation (0, 25 and 50 g). Parameters measured were root colonization, plant height, stem diameter, root drying weight, crown drying weight, crown root ratio, root Pb content, crown Pb content and soil Pb content after harvest.The results showed that Pb addition affected significantly on plant height, Pb content on root, crown and soil after harvesting parameter. Inoculation of mycorrhiza affected significantly on plant height, stem diameter, drying weight of root and crown. Inoculation of mycorrhiza did not significant on Pb content but capable to increasing Pb content on root, crown and soil. The interaction of the two faktors did not affected significantly on all parameters. Key words: Sengon, Pb, AMF